2015
DOI: 10.1002/eqe.2526
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic FE simulation of four‐story steel frame modeled by solid elements and its validation using results of full‐scale shake‐table test

Abstract: Dynamic finite element analyses of a four-story steel building frame modeled as a fine mesh of solid elements are performed using E-Simulator, which is a parallel finite element analysis software package for precisely simulating collapse behaviors of civil and building structures. E-Simulator is under development at the National Research Institute for Earth Science and Disaster Prevention (NIED), Japan. A full-scale shake-table test for a four-story frame was conducted using E-Defense at NIED, which is the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Detailed three-dimensional (3D) finite element models, therefore, would be more appropriate to analyze the test, and they were used by Tada et al [7], Pan et al [8], Miyamura et al [9], and Isobe et al [10]. However, those simulations required large modeling and computational efforts, not really necessary for the most of structural components responding elastically or even inelastically as long as simpler analytical techniques are available.…”
Section: Collapse Experiments and Simulationsmentioning
confidence: 99%
“…Detailed three-dimensional (3D) finite element models, therefore, would be more appropriate to analyze the test, and they were used by Tada et al [7], Pan et al [8], Miyamura et al [9], and Isobe et al [10]. However, those simulations required large modeling and computational efforts, not really necessary for the most of structural components responding elastically or even inelastically as long as simpler analytical techniques are available.…”
Section: Collapse Experiments and Simulationsmentioning
confidence: 99%
“…Miyamura et al report that nonlinear behavior of shaking table test of a 4-story steel building can be replicated by using a fine meshed FE model with solid elements [1]. The authors also report about FE analysis examining a full-scale shaking table test of a 3-story steel structure that is the analytical target of this paper modeling mainly shell elements [2], [3].…”
Section: Introductionmentioning
confidence: 98%
“…Above-referenced three reports [1], [2], [3] do not simulate fracture of members in their analytical procedures. In the referenced report [1], the analytical target was the case wherein a collapse of the structure was observed because of not fracture but local buckling of the firststory columns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need for a high-fidelity model increases for the evaluation of liquefaction, since it is a complicated coupling phenomena of soil and underground water. Yamashita et al [1] and Miyamura et al [2] reported that an analysis model with sufficiently fine mesh of solid elements can accurately reproduce both local damage and overall response when a non-linear constitutive relationship is implemented. Considering their achievements, we expected that the spatial resolution of liquefaction behavior could be improved by using a high-fidelity analysis model.…”
Section: Introductionmentioning
confidence: 99%